¿Ser por azar o producirse por azar?: Una reconstrucción de algunos aspectos de la discusión de Aristóteles contra el materialismo a la luz del problema del azar - Rossi, Gabriela (2011)
In this paper I address some aspects of the discussion of Aristotle against materialism. I take as a starting point the inaugural sentence of phys. B 4, where Aristotle refers to the endoxon that there are things which are (einai), and things which become or are generated (gignesthai) by chance. In the first place, I show that Aristotle would have ascribed to the materialists (especially Empedocles) the opinion that things like animals and plants can be (and not only become) by chance. I shall argue that, in fact, this thesis implies that it is not only the compound that is generated, but also the form or eidos of the living being. To this extent, I propose that there are strong reasons for Aristotle to reject that living beings may be by chance, and to circumscribe chance to that which becomes or is generated. In other words: chance can occur within processes of generation but has nothing to do with the causes and principles of those processes. Thus, this repositioning of chance within the sole field of what becomes is closely connected to the causal priority of the eidos in the processes of generation.